Bird protection devices for overhead power lines and electrical substations – problems of monitoring and evaluating the effectiveness of bird protection measures - Vladimir V. Tsittser; Oleg B. Andreev (Пернатые хищники и их охрана)
Experts point out that “A quarter of all overhead power lines outages are caused by birds, and 86% of grid companies name birds as main problem”. Unfortunately, this is the key factor in the problem of mass death of birds: power engineers are forced to protect lines from birds, while the issue of protecting birds from lines has lower priority. In any case, it all comes down to one question: what should we do?